PROFESSIONAL COMMITMENT OF ACCOUNTANT AND THE COMMITMENT OF PUBLIC ACCOUNTING FIRMS ON AUDITOR’S JOB SATISFACTION - Mathius Tandiontong (Journal of Management and Business, 2015)
The Public Accounting Firms (PAFs) have notoptimally met their user’s expectation in providing high quality auditings services. Many financial scandals that involve public accounting practitioners are still occurring. They make users of auditing service confuse about integrity of Certified Public Accountants. This study aims to obtain empirical evidences in evaluating of the extent to which the professional commitment of accountant and organizational PAFs commitmenaffecton auditor’s job satisfaction. This studyusesan explanatory surveymethod, althoughits detailsalso contain some descriptions, however because it is a relational research, its focus lay on relational explanations among verificative variables. Some operationalized variables are included in this study, consisting ofprofessionalcommitment, organizational commitment, and job satisfactionthat paymore fundamental emphasis on their indicators. Datawere collected throughquestionnaire distributionto targetedrespondents, as well aslimitedinterviewsor documentary studies as additional efforts to obtain explanatory elements from survey findings. Analytical units in this study involved the Public Accounting Firms (PAFs) in Indonesia with total population as 417 PAFs. Samplings by a simple proportional randomized method in 79PAFs with 347 accountants as responding target weresent questionnaires. Data analytical and testing methods were carried out by the Structural Equation Modeling (SEM) analysis. The research findings showed that professional commitment of accountants and commitment of the PAFs organization affects auditor’s job satisfaction, both simultaneously or partially.